2011
DOI: 10.1007/s12560-011-9060-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Drip Irrigation Method, Soil, and Virus Type on Tomato and Cucumber Contamination

Abstract: The goal of this study was to better quantify the degree of viral contamination of tomato and cucumber in relationship to virus type, soil type, and irrigation method. Tomatoes and cucumbers were grown in ten-gallon (37.8 L) buckets filled with Pima clay loam or Brazito sandy loam soils. Plants were irrigated with secondary wastewater effluent using surface drip irrigation or subsurface drip irrigation. At specified time intervals irrigation water was seeded with bacteriophages MS-2 and P22, poliovirus type 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
5
0
2
Order By: Relevance
“…Common for the average level is when water is applied on the surface, close to the roots of the plants -for example through tubes. The basic level refers to common surface methods such as sprinklers and flood irrigation, which have been shown to contribute to crop contamination (Alum, Enriquez, & Gerba, 2011;Gerba & Choi, 2006;Stine, Song, Choi, & Gerba, 2005).…”
Section: Preventive Control Activitiesmentioning
confidence: 99%
“…Common for the average level is when water is applied on the surface, close to the roots of the plants -for example through tubes. The basic level refers to common surface methods such as sprinklers and flood irrigation, which have been shown to contribute to crop contamination (Alum, Enriquez, & Gerba, 2011;Gerba & Choi, 2006;Stine, Song, Choi, & Gerba, 2005).…”
Section: Preventive Control Activitiesmentioning
confidence: 99%
“…The authors suggested that this might be due to the interaction of the virus with particulate or soluble matter present in the waste water, but absent in the irrigation water, preventing their entrance into the roots. Alum et al (2011) studied the effectiveness of drip irrigation in the control of viral contamination of salad crops (tomato and cucumber) in a greenhouse in potted plants. The plants were irrigated with secondary effluent using surface drip and subsurface irrigation.…”
Section: Contamination Of Produce During Irrigationmentioning
confidence: 99%
“…The most commonly used application techniques are spraying and dripping. Irrigation by furrows, although considered a rudimentary form of agricultural crop irrigation, can currently be considered among the most appropriate when dealing with raw wastewater because it presents a low risk of blocking emitters by chemical, physical and biological agents compared to local applications 3 5 . This method also presents better sanitation safety, without contamination of plants and system operators compared to application by spraying 6 .…”
Section: Introductionmentioning
confidence: 99%